Γ-Aminobutyric acid-rich yogurt fermented by Streptococcus salivarius subsp. thermophiles fmb5 apprars to have anti-diabetic effect on streptozotocin-induced diabetic mice. (January 2016) - Chen, Lin; Zhao, Haizhen; Zhang, Chong; Lu, Yingjian; Zhu, Xiaoyu; Lu, Zhaoxin
Highlights: GABA-rich yogurt fermented is orally administrated to SIDM for the first time. Oral administration of GABA-rich yogurt ameliorates hyperglycaemia of SIDM. Oral administration of GABA-rich yogurt improves impaired glucose tolerance of SIDM. Oral administration of GABA-rich yogurt improves dyslipidaemia of SIDM. GABA-rich yogurt enhances the level of serum insulin and restores pancreas of SIDM. Abstract: γ-Aminobutyric acid (GABA)-rich yogurt is a novel type of functional fermented-dairy product in the market. This study investigated the anti-diabetic effects of GABA-rich yogurt fermented by Streptococcus salivarius subsp. thermophiles fmb5 on streptozotocin-induced diabetic mice (SIDM). SIDM was administered orally GABA-rich yogurt for six weeks. The results showed that oral administration of GABA-rich yogurt improved both hyperglycaemia and impaired glucose tolerance of SIDM with a dose-dependent effect. Notably, GABA-rich yogurt significantly decreased the concentrations of serum total cholesterol (TC) and triacylglycerol (TG), whereas remarkably increased the concentrations of high-density lipoprotein cholesterol (HDL-C) and insulin in serum of SIDM. Furthermore, GABA-rich yogurt normalised hypertrophy of liver and kidney and restored pancreas islet in SIDM. These results suggest that GABA-rich yogurt may be effective in improving type 1 diabetes (T1D) and delaying the progression of diabetes complications. GABA-rich yogurt could be a great functional dairy product with benefit for T1D patients.